Validation of Chromatographic Methods: Checking the Peak Purity and the Specificity of Methods with Diode Array Detectors (Review) - N. A. Epshtein (Разработка и регистрация лекарственных средств)
Introduction. When developing and validating methods of impurity determination, it is important to test the spectral peak purity (SPP) of the main substances using diode array detectors (DAD).Text. It is emphasized that the task of testing SPP is to detect invisible coeluting impurities under the peak of the main substance, and not the control the absolute purity of the peak. SPP testing reduces the risk of getting non enough specific methods. In this regard, we considered the main criteria and key points for assessing the spectral purity of peaks when using computer programs of Agilent's, Shimadzu's, and Waters's chromatographs. Conclusion. Recommendations are given, which should be taken into account for the correct assessment of spectral purity of peaks during development of chromatographic methods and validation of their specificity.